Molecular energetics of 4-methyldibenzothiophene: An experimental study - Vera L S Freitas (2010)
The standard (p degrees = 0.1 MPa) molar enthalpy of formation of 4-methyldibenzothiophene, in the gaseous phase, at T = 298.15 K, was derived from the combination of the values of the standard molar enthalpy of formation, in the crystalline phase, at T = 298.15 K, and the standard molar enthalpy of sublimation, at the same temperature. The standard molar enthalpy of formation in the crystalline phase, determined from the standard massic energy of combustion, in oxygen, is (70.9 +/- 4.8) kJ . mol(-1) and was measured by rotating-bomb combustion calorimetry. From Calvet microcalorimetry measurements, the standard molar enthalpy of sublimation obtained is (90.3 +/- 0.7) kJ . mol(-1).